Tinjauan Hukum Terhadap Putusan Kasasi Mahkamah Agung Nomor 836K/PDT.SUS-HKI/2022 Mengenai Sengketa Merek Antara Starbucks Corporation Dan PT Sumatra Tobacco Trading Company - Sania Akalila Putri Thahir; Rika Ratna Permata; Ranti Fauza Mayana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The registration of trademarks with the “first to file” constitutive system, adopted by Indonesia, is often abused by trademark owners with malicious intent by first registering their trademarks that are similar to well-known trademarks, knowing that the well-known trademarks have not been registered in Indonesia. This was the case with the “Starbucks” trademark owned by Starbucks Corporation in Decision Number 836 K/Pdt.Sus-HKI/2022. Starbucks Corporation filed a lawsuit for the cancellation of “Starbucks” trademark in class 34 owned by Sumatra Tobacco Trading Company on the grounds of similarity to a well-known trademark for a different class and the malicious intent to exploit the reputation of the “Starbucks